2,8-Dimethyltricyclo[5.3.1.1(3,9)]dodecane-syn-2,syn-8-diol–propanoic acid (1/1) - Mizobe, Yuji (International Union of Crystallography, 2009)
The racemic title compound, C(14)H(24)O(2)·C(3)H(6)O(2), crystallizes in the monoclinic space group P2(1)/c as a 1:1 diol/carboxylic acid cocrystal, A–B. The lattice incorporates infinite chains of the alcohol–carboxylic acid–alcohol supramolecular synthon, (⋯O—H⋯O=C(R)—O—H⋯O—H⋯), in which the hydrogen-bonded molecules (A—B—A)(n) surround a pseudo-threefold screw axis. The carboxylic acid group functions like an extended alcohol hydroxy group. Each diol, A, takes part in two such threefold screw arrangements, leading to a hydrogen-bonded layer structure, with adjacent layers containing diol molecules of opposite handedness. The central C atom of the propano bridge is disordered over two sites of occupancies 0.75 (1) and 0.25 (1). The methyl group of the propanoic acid molecule is disordered over two sites of occupancies 0.68 (1) and 0.32 (1).